2010
DOI: 10.1136/emj.2009.078014
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of important neurological causes of dizziness among patients presenting to the emergency department

Abstract: Most dizzy patients had benign causes. Several clinical factors favoured a diagnosis of central neurological causes of dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
65
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 7 publications
7
65
2
4
Order By: Relevance
“…Based on the results of previous studies and expected rates of outcomes, the following clinical factors were chosen a priori as potential predictors of outcomes: age, imbalance as the reference triage symptom, isolated dizziness symptoms (eg, no other associated neurologic or systemic symptoms), positional symptoms, previous stroke, diabetes mellitus, Dix-Hallpike maneuver, and focal examination abnormalities (any neurologic sign besides nystagmus). [6][7][8]10,13 Logistic regression was used to evaluate the association between these prespecified factors and the primary outcome. Of these 8 prespecified factors, those that were significantly (PϽ.10) associated with the outcome in univariate analysis (age, imbalance as the triage symptom, isolated dizziness, previous stroke, and focal examination abnormalities) were forced into the final multivariate model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the results of previous studies and expected rates of outcomes, the following clinical factors were chosen a priori as potential predictors of outcomes: age, imbalance as the reference triage symptom, isolated dizziness symptoms (eg, no other associated neurologic or systemic symptoms), positional symptoms, previous stroke, diabetes mellitus, Dix-Hallpike maneuver, and focal examination abnormalities (any neurologic sign besides nystagmus). [6][7][8]10,13 Logistic regression was used to evaluate the association between these prespecified factors and the primary outcome. Of these 8 prespecified factors, those that were significantly (PϽ.10) associated with the outcome in univariate analysis (age, imbalance as the triage symptom, isolated dizziness, previous stroke, and focal examination abnormalities) were forced into the final multivariate model.…”
Section: Discussionmentioning
confidence: 99%
“…14 Our results are also consistent with those of previous studies, which found low rates of serious neurologic diagnoses in ED patients with dizziness. 3,[6][7][8][9][10]13 A prospective analysis of 413 adults with dizziness presenting to a Hong Kong ED found a central neurologic cause in 6% of patients, although this study may have underestimated the number of patients with posterior fossa lesions since diagnoses were made using CT only. 10 Similarly, a population-based study of 1666 mostly Mexican American patients presenting with dizziness to EDs in Corpus Christi, Texas, demonstrated an incidence of stroke or TIA of 3.2% (this study assessed for acute cerebrovascular disorders only).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations